2018
DOI: 10.5588/ijtld.17.0167
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial lung disease and risk of mortality: 11-year nationwide population-based study

Abstract: ILD patients had a significantly higher risk of death than matched controls, after adjustment for potential confounders and comorbidities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…On the other hand, it is possible that we could underestimated the incidence of ILD, because of inaccurate data especially in asymptomatic patients with ILD, Also, ILD outcomes should be affected by treatment, a variable that we could not include in our study. Nevertheless previous studies using database data in USA [42] and in Asia [41] reported similar results. Although SNHDD have some limitations, it has a great advantage that it is mandated by the National Public Health System, and it includes almost 100% of admission in Spain and it is periodically audited.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…On the other hand, it is possible that we could underestimated the incidence of ILD, because of inaccurate data especially in asymptomatic patients with ILD, Also, ILD outcomes should be affected by treatment, a variable that we could not include in our study. Nevertheless previous studies using database data in USA [42] and in Asia [41] reported similar results. Although SNHDD have some limitations, it has a great advantage that it is mandated by the National Public Health System, and it includes almost 100% of admission in Spain and it is periodically audited.…”
Section: Discussionsupporting
confidence: 68%
“…They also found that lung cancer and bacterial pneumonia influenced on IHM in patients with idiopathic pulmonary fibrosis. In a recent Korean study, based on ICD codes like ours, Choi et al [41] also observed that patients with ILD have a significantly higher risk of death than matched controls.…”
Section: Discussionmentioning
confidence: 60%
“…The presence of fibrosing interstitial pneumonia in RA patients is associated with a lower survival rate than that of RA alone [34], and CTD-ILD has a poorer prognosis than idiopathic interstitial pneumonia [19]. ILD-only also revealed higher mortality than non-ILD control [35]. In contrast, several studies have shown opposite or neutral results in relation to survival [3640].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with ILD are often asymptomatic until the lesion progresses significantly. Interstitial pulmonary abnormality (ILA), which is considered to be an early lesion of interstitial lung disease, has a higher mortality rate than patients without ILA [ 3 ] as well as ILD [ 4 ]. Furthermore, in patients with ILD, a study using health insurance claim data found that lung cancer incidence is higher than chronic obstructive pulmonary disease (COPD) [ 5 ].…”
Section: Introductionmentioning
confidence: 99%